Dysphagia and obstructive sleep apnoea in post-extubated intensive care unit patients - Javed, Sidra; Ashraf, Anum; Mumtaz, Nazia; Saqulain, Ghulam (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the relationship between dysphagia and obstructive sleep apnoea and its association with age, gender and Glasgow Comma Scale in post-extubated patients in an intensive care setting. Method: The correlational study was conducted from July 1 to October 31, 2021, at the intensive care unit of Evercare Hospital, Lahore, Pakistan, and comprised post-extubated patients of either ender aged 45-70 years within 72 hours following extubation and having Glasgow comma scale score 11-15. Gugging Swallowing Screen and Obstructive Sleep Apnoea questionnaires were used for data collection. Data was analysed using SPSS 25. Results: Of the 29 patients with a mean age of 57.45±8.74 years, 18(62.1%) were males. There was a significant correlation between dysphagia and obstructive sleep apnoea (p=0.005). The Obstructive Sleep apnoea score had a significant negative correlation with Glasgow Coma Scale score (p=0.01), while dysphagia revealed a significant positive correlation (p<0.001) with Glasgow Coma Scale score. Age and gender had no significant association with either dysphagia or obstructive sleep apnoea (p>0.05). Conclusion: There was a significant correlation between dysphagia and obstructive sleep apnoea in post-extubated patients under intensive care. Both dysphagia and obstructive sleep apnoea had a significant correlation with Glasgow Comma Scale score. Key Words: Dysphagia, Berlin questionnaire, Gugging swallowing screen, Glasgow comma scale, Obstructive sleep apnoea, Post-extubation.